Current Pharmacological and Non-Pharmacological Therapies for Chronic Cough (Canadian Allergy & Immunology Today, 2022)
Chronic cough, defined as cough lasting 8 weeks or longer, affects approximately 10% of adults globally, but with large global variations with prevalence estimates ranging from 2–18%. The prevalence of chronic cough in adults over the age of 45 in the Canadian Longitudinal Study of Ageing (CLSA) was 16%, the second highest in the world. Interestingly, the prevalence and incidence is higher in English speaking compared with French speaking participants. Cough is the leading cause for ambulatory and primary care visits to physicians and one of the most common reasons for referral to specialist care. Chronic cough is associated with aging, smoking, higher body mass index, use of an ACE-inhibitor, and airways diseases. More recently, novel data has shown that symptoms of depression and psychological distress independently increase the risk of developing chronic cough by approximately 20%. Data from clinical trials and observational cohort studies suggest that patients with chronic cough have a median cough frequency of 20 coughs/hr. This may lead to distressing physical, psychological and social consequences such as urinary incontinence, exhaustion, fatigue, anxiety, frustration, embarrassment and social isolation, which all impairs quality of life. Chronic cough can be challenging to treat, since most over-the-counter therapies are ineffective and current treatments for chronic cough are all considered ‘off-label’. Although most cases are due to a benign cause, chronic cough can represent a serious underlying condition. A recent Canadian consensus has identified a simplified approach which can aid in the management of chronic cough and provide treatment for refractory or unexplained chronic cough. The guiding principles of this approach include i) investigation to rule out serious underlying conditions, ii) objective testing to prevent over and under-diagnosis, iii) treatment of identifiable diseases and traits and iv) monitoring to ensure effectiveness of treatment, including minimization of side effects and appropriate titration of treatment.